Meaning Reconstruction in Fairy Tales Across Eras: An Intertextual Study on A Grain of Truth and Beauty and the Beast - Jilan, Muhammad Fa’iz; Haryati, Rahayu Puji (Language Circle: Journal of Language and Literature, 2024)
Intertextuality is a study that observes the relation and connection that text has with other texts. By looking at intertextuality, it can be seen how one text can have resemblances to another text, whether that resemblance is intentional or not. This study uses a story by Andrzej Sapkowski, titled A Grain of Truth as the material objects of the study. It tells the story of a cursed human with a monstrous body who desires to find love to be human again. This research uses qualitative research methods, and the data were analyzed using intertextuality theory to answer the research questions. This paper aims at finding out the intertextuality connection between A Grain of Truth and Beauty and the Beast, through their resemblances in theme and due to the sociocultural enironment erround the stories. The result shows that there are sesemplances in terms of theme, characterization, and symbols in the story. This is related to the collective unconsciousness about the perception of love and curse in fantasy.